2022
DOI: 10.1021/acs.orglett.2c03904
|View full text |Cite
|
Sign up to set email alerts
|

Deaminative Cyclization of Tertiary Amines for the Synthesis of 2-Arylquinoline Derivatives with a Nonsubstituted Vinylene Fragment

Abstract: With triethylamine as a vinylene source, a convenient protocol for the regioselective synthesis of β,γ-nonsubstituted 2arylquinolines from aldehydes and arylamines has been accomplished. The deaminative cyclization is also extended to long-chain tertiary alkylamines, enabling diverse alkyl groups to be concurrently installed into the pyridine rings. This process demonstrates a new conversion pathway for the simultaneous dual C(sp 3 )−H bond functionalization of tertiary amines, wherein the transient acyclic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Moreover, only a trace amount of product 3a was found in the absence O 2 (Scheme 7d), which suggested that O 2 plays an essential role in the annulation procedure. According to the mechanistic investigations above and previous literature, a plausible explanation of the reaction mechanism is depicted in Scheme 20 Finally, the desired product 3 is produced through oxidative aromatization of O 2 .…”
Section: Scheme 5 Synthesis Of Phthalimides In One Pot Amentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, only a trace amount of product 3a was found in the absence O 2 (Scheme 7d), which suggested that O 2 plays an essential role in the annulation procedure. According to the mechanistic investigations above and previous literature, a plausible explanation of the reaction mechanism is depicted in Scheme 20 Finally, the desired product 3 is produced through oxidative aromatization of O 2 .…”
Section: Scheme 5 Synthesis Of Phthalimides In One Pot Amentioning
confidence: 93%
“…The amide carbonyl α carbon nucleophilic attack on the imine cation causes cyclization into intermediate E . The Mannich-type intermediate E could be transformed into intermediate G via elimination of Et 2 NH at high temperature . Finally, the desired product 3 is produced through oxidative aromatization of O 2 .…”
mentioning
confidence: 99%
“…14 In addition, trialkylamines can be used as carbon sources to participate in the reaction and provide ethyl or methyl. 15 However, studies on trialkylamines as carbon sources have mostly focused on the construction of nitrogen-containing heterocycles. The use of trialkylamines to provide carbon chains in the synthesis of 2,3-diamines has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cleaving the highly stable C–N bond in tertiary amines and applying the fragments to construct new C–N or C–C bonds have aroused much attention. However, previous investigations mainly focused on transition-metal catalysis processes. In contrast, non-transition-metal catalysis for the activation of C–N bond has been rarely explored. Based on our previous work on β-ketoamides, herein, we present a simple and efficient protocol toward oxalamides by the reaction of β-ketoamides with tertiary amines via the tandem oxidation/amination process (Scheme d).…”
Section: Introductionmentioning
confidence: 99%